Insights into Regulation and Function of the Major Stress-Induced hsp70 Molecular Chaperone In Vivo: Analysis of Mice with Targeted Gene Disruption of the hsp70.1 or hsp70.3 Gene - Huang, Lei (American Society for Microbiology, 2001)
The murine hsp70 gene family includes the evolutionarily conserved hsp70.1 and hsp70.3 genes, which are the major proteins induced by heat and other stress stimuli. hsp70.1 and hsp70.3 encode identical proteins which protect cells and facilitate their recovery from stress-induced damage. While the hsp70 gene family has been widely studied and the roles of the proteins it encodes as molecular chaperones in a range of human pathologies are appreciated, little is known about the developmental regulation of hsp70.1 and hsp70.3 expression and the in vivo biological function of their products. To directly study the physiological role of these proteins in vivo, we have generated mice deficient in heat shock protein 70 (hsp70) by replacing the hsp70.1 or hsp70.3 gene with an in-frame β-galactosidase sequence. We report here that the expression of hsp70.1 and hsp70.3 is developmentally regulated at the transcriptional level, and an overlapping expression pattern for both genes is observed during embryo development and in the tissues of adult mice. hsp70.1(−/−) or hsp70.3(−/−) mice are viable and fertile, with no obvious morphological abnormalities. In late embryonic stage and adult mice, both genes are expressed constitutively in tissues exposed directly to the environment (the epidermis and cornea) and in certain internal organs (the epithelium of the tongue, esophagus, and forestomach, and the kidney, bladder, and hippocampus). Exposure of mice to thermal stress results in the rapid induction and expression of hsp70, especially in organs not constitutively expressing hsp70 (the liver, pancreas, heart, lung, adrenal cortex, and intestine). Despite functional compensation in the single-gene-deficient mice by the intact homologous gene (i.e., hsp70.3 in hsp70.1(−/−) mice and vice versa), a marked reduction in hsp70 protein expression was observed in tissues under both normal and heat stress conditions. At the cellular level, inactivation of hsp70.1 or hsp70.3 resulted in deficient maintenance of acquired thermotolerance and increased sensitivity to heat stress-induced apoptosis. The additive or synergistic effects exhibited by coexpression of both hsp70 genes, and the evolutionary significance of the presence of both hsp70 genes, is hence underlined.